Demonstration of P-selectin expression and potential function in human corneal epithelial cells. (November 2018) - Gillies, Peter J.; Richardson, Neil A.; Walshe, Jennifer; Stephenson, Sally-Anne; Dawson, Rebecca A.; Harkin, Damien G.
Abstract: In response to an unexpected observation of apparent localisation by immunocytochemistry, we have investigated the potential expression and function of P-selectin (CD62P) in human corneal epithelial cells. The SV40 immortalised cell line, HCE-T (validated by STR profiling), along with multiple donor corneal-limbal tissue samples, were examined for P-selectin expression using a combination of immunocytochemistry, Western blotting, RT-PCR and immunohistochemistry. Potential expression of the major ligand for P-selectin (P-selectin glycoprotein ligand-1; PSGL-1; CD162) was also examined by immunocytochemistry and RT-PCR. A selective inhibitor of P-selectin-PSGL-1 binding (KF38789) was subsequently tested for effects on HCE-T cells using a cell culture gap-closure assay. HCE-T cells as well as primary epithelial cultures derived from donor corneal-limbal tissue, displayed positive immunostaining for P-selectin. Staining was particularly evident at cell-cell boundaries and at the outer edge of expanding epithelial islands. P-selectin expression was confirmed by Western blotting and RT-PCR (validated by product sequencing), as well as by immunohistochemistry performed on serial sections of corneal-limbal tissue stained for P-selectin, keratin 3 and p63. PSGL-1 was detected by RT-PCR and immunocytochemistry in both corneal epithelial cells as well as human limbal fibroblasts (HLF). KF38789 (5 μM) significantly reduced closure of a 500-μm gap between confluent sheets of HCE-T cells over an 8-hr period (by ∼40%, p < 0.01; paired two-tailed T test), but had no effect on culture gap-closure by either HLF or murine 3T3 fibroblasts. These results provide evidence of P-selectin expression in human corneal epithelial cells and suggest a potential role for this glycoprotein in facilitating the net movement of confluent sheets of human corneal epithelial cells. Highlights: Human corneal epithelial (HCE) cells express P-selectin in vitro and in situ . HCE and limbal fibroblasts both appear to express the P-selectin ligand, PSGL-1. An inhibitor of P-selectin binding to PSGL-1 reduces HCE migration in vitro . These findings suggest a potential new role for P-selectin within the cornea.